Multidimensional measure of energy poverty in Lesotho - Lehema, Nthati ‘Mabatho (University of the Witwatersrand, Johannesburg, 2024)
This study employs the Alkire-Foster methodology to assess multidimensional energy poverty in Lesotho, using data from the Household Energy Consumption Survey in Lesotho. The investigation considers three dimensions, cooking, lighting, and water heating in constructing the multidimensional energy poverty index. In terms of the three dimensions, the overall findings indicate that at the national level, approximately 61% of the households experience multidimensional energy poverty. Upon decomposing the Multidimensional Energy Poverty Index (MEPI) by the settlement type, the results indicate that 83.50% of the households in rural areas are multidimensionally energy poor while 51.20% of the peri-urban households are deprived. In the urban areas, only 19% of the households experience energy poverty. In decomposing the MEPI by the gender of the household head, the results demonstrate that around 59.40% of female-headed households exhibit multidimensional energy poverty than their male-headed counterparts with 54.40%, with an average intensity of 91% of the weighted indicators. Decomposition by districts reveals that Butha-Buthe, Mokhotlong, Qacha, and Thaba-Tseka have over 80% of the multidimensionally poor households. Additionally, the study highlights the prevalence of traditional cooking fuels in rural areas, with minimal reliance on electricity. This pattern shifts with urbanization, where traditional fuel consumption decreases.
A research report submitted in fulfillment of the requirements for the Master of Commerce (Environmental and Energy Economics), In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Multidimensional energy poverty; Access; Alkire-Foster Methodology; SDG-13: Climate action